Prehistoric Marine Resource Use in the Indo-Pacific Regions - Ono, Rintaro (Terra Australis, 2013)
Although historic sources provide information on recent centuries, archaeology can contribute longer term understandings of pre-industrial marine exploitation in the Indo-Pacific region, providing valuable baseline data for evaluating contemporary ecological trends. This volume contains eleven papers which constitute a diverse but coherent collection on past and present marine resource use in the Indo-Pacific region, within a human-ecological perspective. The geographical focus extends from Eastern Asia, mainly Japan and Insular Southeast Asia (especially the Philippines) to the tropical Pacific (Micronesia, Melanesia, and Polynesia) and outlying sites in coastal Tanzania (Indian Ocean) and coastal California (North Pacific). The volume is divided thematically and temporally into four parts: Part 1, Prehistoric and historic marine resource use in the Indo-Pacific Region; Part 2, Specific marine resource use in the Pacific and Asia; Part 3, Marine use and material culture in the Western Pacific; and Part 4, Modern marine use and resource management.